Commentary: on the debate on ethics in African archaeology - Haber, Alejandro (2014)
While commenting on the debate on ethics in African archaeology, this paper asks for a contextualisation of archaeological practice in territorial entanglements where capital, state and science — including archaeology — meet with local territorial agencies in encounters that work as battlegrounds where globalised discourses and practices (corporations, states, science) intervene in local territories, communities and knowledge. By codifying epistemic violence within its built-in assumptions, the archaeological discipline, has already taken fundamental ethical decisions regarding the Other. In order to decolonise archaeology an un-disciplining from those epistemic assumptions is needed. Such tasks may be aided by informing epistemic interests with local knowledge. Cet article offre un commentaire sur les débats entourant la déontologie en archéologie africaine, et préconise une contextualisation de la pratique archéologique dans le cadre des enchevêtrements territoriaux. Capital, état et science (y compris l'archéologie) y confrontent les agences territoriales locales dans des rencontres qui deviennent des champs de bataille, où les pratiques et discours globalisants (corporations, états, science) interviennent dans les territoires, communautés, et savoirs locaux. En codifiant la violence épistémique dans ses préconceptions, l'archéologie a d'ores et déjà pris des décisions éthiques fondamentales en ce qui concerne l'Autre. Afin de décoloniser l'archéologie, il nous faut nous ‘dé-discipliner’ de ces préconceptions épistémiques. Une telle tâche peut être facilitée si l'on combine le savoir local avec les intérêts épistémiques.